(untitled) (SCIENCE TIME JOURNAL, 2026)
This article explores the construction of hybrid identity in Pakistani diasporic fiction through a comparative analysis of the works of Kamila Shamsie and Mohsin Hamid. Drawing on the theoretical perspectives of Homi K. Bhabha, Stuart Hall, and Gloria Anzaldúa, the study examines how the authors represent issues of belonging, displacement, cultural negotiation, and identity formation in an increasingly globalized world. Particular attention is paid to Shamsie’s “Burnt Shadows” and “Home Fire”, as well as Hamid’s “The Reluctant Fundamentalist” and “Exit West”. The analysis demonstrates that both writers portray characters situated between Pakistani and Western cultural spheres, whose identities emerge through continuous processes of adaptation and negotiation.